2022
DOI: 10.1186/s43042-022-00287-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and population genetic data of colour vision deficiency among students from selected tertiary institutions in Lagos State, Nigeria

Abstract: Background Colour vision deficiency (CVD), also referred to as colour blindness, is the failure or decreased ability to distinguish between certain colours under normal lighting conditions. It is an X-linked genetic disorder with varying degrees of prevalence in different populations. There is presently no report on the prevalence of CVD among students of the selected tertiary institution. Hence, the present study was aimed at determining the occurrence and genetics of CVD among students from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…A significant correlation between female sex and deutan color blindness was observed. In contrast to our results, Fakorede et al reported that the percentage of males suffering from deutan colour blindness (2.33%) is higher than that of females suffering from this type of blindness (0.79%) [ 25 ]. Another study noted a greater prevalence of deutan and protan defects in males than in females [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A significant correlation between female sex and deutan color blindness was observed. In contrast to our results, Fakorede et al reported that the percentage of males suffering from deutan colour blindness (2.33%) is higher than that of females suffering from this type of blindness (0.79%) [ 25 ]. Another study noted a greater prevalence of deutan and protan defects in males than in females [ 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Color vision deficit (CVD), a collection of diseases that impact colour perception, affects around one in 12 males and one in every 200 women worldwide. The most prevalent cause of CVD is X-linked chromosomal inheritance [22]. It can also be acquired through chronic illnesses that damage the retina, optic nerve, and brain, such as diabetes mellitus, sickle cell anaemia, and retinitis pigmentosa, or through the use of certain medications such as sildenafil, digoxin, ethambutol, furosemide, metronidazole, and some antimalarials, but the most common cause of colour blindness is a hereditary defect in the development of one or more [15].…”
Section: Resultsmentioning
confidence: 99%
“…The inability to distinguish between different colors under normal lighting conditions is known as colour vision deficiency (CVD) (Kundu & Chakma, 2020). According to earlier studies, approximately 8%-9% of men and 0.5% of women are reported to be colorblind (Fakorede et al, 2022).…”
Section: Introductionmentioning
confidence: 97%